EPIDEMIOLOGY OF TRAUMA IN THE EMERGENCY ROOM OF BALI JIMBARAN HOSPITAL: RISK FACTORS AND SEVERITY IN A PREVENTIVE, RETROSPECTIVE CROSS-SECTIONAL FRAMEWORK - Sholahudin, Iqbal; Budianto, Aries (Universitas Brawijaya, 2025)
Trauma is the main cause of morbidity and mortality, especially due to traffic accidents in Indonesia. Bali, as an international tourist destination, faces a high risk of trauma cases, but epidemiological data is still limited. This study aims to analyze the distribution of trauma cases in the emergency room of Bali Jimbaran Hospital and the relationship between risk factors and patient severity. The research design used a cross-sectional retrospective observational analytical study with a total of 6,600 medical records of emergency room patients for the period November 2024–May 2025, of which 1,714 cases were identified as trauma. Independent variables include the type of incident, time of occurrence, and payment method, while the severity of trauma is a dependent variable. The analysis was carried out using chi-square tests, Spearman's rho, and logistic regression. The results showed that the majority of trauma patients were in the moderate (55.4%) category, followed by severe (23.3%) and mild (21.4%). Most patients were of productive age (19–45 years; 42.8%) with a predominance of general surgery cases (52%). Night time was shown to be significantly correlated with severe trauma (p=0.027), while payment methods were not associated with severity (p=0.890). The majority of patients use the BPJS (37.8%) and self-payment (34.8%). In conclusion, the timing factor plays a role in the severity of trauma, while the financing mechanism does not affect clinical outcomes. These findings emphasize the need for driving safety education, optimizing emergency room data recording, increasing the use of special insurance, and strengthening emergency room capacity in tourist areas.